Functional dyspepsia: new pathophysiologic knowledge with therapeutic implications - Hernando-Harder, Ana C.; Franke, Andreas; Singer, Manfred V.; Harder, Hermann (Medicina, 2007)
Functional dyspepsia (FD) is a heterogeneous, highly prevalent symptom complex in the community and general practice. FD is defined as the presence of symptoms considered as originated in the gastroduodenal region, in the absence of any organic, systemic, or metabolic disease that is likely to explain the symptoms. Pathogenetic features include disturbed gastric accommodation and emptying, duodenal dysmotility, heightened sensitivity, notably psychosocial disturbances and an association with a postinfective state. Increasing efforts are made to determine the etiopathogenesis of the disease, including new molecular and genetic aspects. However, the exact etiopathologic mechanism that causes the symptoms in an individual patient remains to be identified. The new Rome III criteria redefine and sub-characterize FD patients according to their main symptoms and this can be of value for standardized research, development and control of new therapeutic strategies and calculated therapeutic recommendations in the clinical practice. Various treatment modalities have been employed including dietary modifications, pharmacological agents directed at different targets within the gastrointestinal tract and central nervous system and psychological therapies including hypnotherapy. Unfortunately, to date, all of these therapies have yielded only marginal results. After excluding organic diseases, it is essential that the patient be assured about the benign nature and prognosis of the disease, and this can be sometimes the most helpful inversion for the patient and his/her physician.